2019
DOI: 10.2298/fil1918777s
|View full text |Cite
|
Sign up to set email alerts
|

Connections between Hv-S-act, GHS-act and S-act

Abstract: The largest class of hyperstructures is the one which satisfies the weak properties and they are called H v-structures. In this paper, the concept of H v-S-act is introduced and some of their properties are investigated. The present paper establishes a possible connection between S-act, GHS-act and H v-S-act. It is shown that the quotient of GHS-act with any equivalence relation is H v-S-act. The main tool to study all hyperstructures is the fundamental relations. The study of fundamental relations in H v-S-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
1
0
3
Order By: Relevance
“…In such a circumstance, liability is limited by most of the statutes to the directors, secretaries, managers, or other officers whose acts resulted in the breach. 51 Where the offender does not fall into any of these categories of officers, he escapes without liability. 52 It is suggested that liability be imposed on the corporate body and on any individual whose act or omission caused the breach, irrespective of the status of that person in the organisation.…”
Section: The Consumer Protection Council Act 2004 19mentioning
confidence: 99%
“…In such a circumstance, liability is limited by most of the statutes to the directors, secretaries, managers, or other officers whose acts resulted in the breach. 51 Where the offender does not fall into any of these categories of officers, he escapes without liability. 52 It is suggested that liability be imposed on the corporate body and on any individual whose act or omission caused the breach, irrespective of the status of that person in the organisation.…”
Section: The Consumer Protection Council Act 2004 19mentioning
confidence: 99%
“…Pode ser responsável por atrair pessoas de todos os modos de transporte, diminuindo uso de automóvel particular, de táxis e aliviando a ocupação do transporte público (SHAHEEN;COHEN, 2013) ou aumentando uso de transportes ativos em geral (FISHMAN; HAWORTH, 2015).…”
Section: Sistemas De Bicicletas Públicas Compartilhadasunclassified
“…Um estudo em Montreal estimou que a nova oferta de bicicletas ocasionou uma diminuição de viagens diárias de automóvel, mas enfatiza que a maioria fez a troca vindo do transporte público (FULLER et al, 2013). Na região metropolitana de Minneapolis-Saint Paul, Estados Unidos, também conhecida por Cidades Gêmeas, houve um aumento das viagens sobre trilhos, com integração com a bicicleta compartilhada (SHAHEEN;COHEN, 2013).…”
Section: Sistemas De Bicicletas Públicas Compartilhadasunclassified
See 1 more Smart Citation